2015
DOI: 10.1371/journal.ppat.1004481
|View full text |Cite
|
Sign up to set email alerts
|

Control of Murine Cytomegalovirus Infection by γδ T Cells

Abstract: Infections with cytomegalovirus (CMV) can cause severe disease in immunosuppressed patients and infected newborns. Innate as well as cellular and humoral adaptive immune effector functions contribute to the control of CMV in immunocompetent individuals. None of the innate or adaptive immune functions are essential for virus control, however. Expansion of γδ T cells has been observed during human CMV (HCMV) infection in the fetus and in transplant patients with HCMV reactivation but the protective function of γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 48 publications
(68 reference statements)
5
64
0
Order By: Relevance
“…110 During secondary infection, cells proliferate and resolve infection Table 1. 111,112 These results suggest that cd T cells are important mediators of protection against CMV and support approaches using adoptive transfer of effector/memory cd T cells or targeting cd T cells in future CMV vaccine trials. 102 Several studies in mice have shown that (1) cd T cells are capable of protecting ab T-cell-deficient mice against CMV-induced pathology and (2) adoptive transfer of CMV-induced cd T cells provides long-term protection in immunodeficient mice.…”
Section: Viral Infectionsmentioning
confidence: 56%
“…110 During secondary infection, cells proliferate and resolve infection Table 1. 111,112 These results suggest that cd T cells are important mediators of protection against CMV and support approaches using adoptive transfer of effector/memory cd T cells or targeting cd T cells in future CMV vaccine trials. 102 Several studies in mice have shown that (1) cd T cells are capable of protecting ab T-cell-deficient mice against CMV-induced pathology and (2) adoptive transfer of CMV-induced cd T cells provides long-term protection in immunodeficient mice.…”
Section: Viral Infectionsmentioning
confidence: 56%
“…The detection of infected cells was facilitated by reporter viruses. For live imaging (MCMV-LUC), an HCMV IE1 promoterdriven luciferase expression cassette was inserted into m157 of a bacterial artificial chromosome (BAC)-cloned MCMV strain Smith genome that also was repaired for MCK2 expression (25). For fluorescent labeling of infected cells (MCMV-GR), an HCMV IE1 promoter-driven cassette was inserted into m157 of MCMV strain K181 by homologous recombination.…”
Section: Methodsmentioning
confidence: 99%
“…Suggestive evidence indicates that cd T cells are involved in diverse aspects of the host response, including acute and/or chronic inflammation, effective wound healing and the killing of virusinfected, cancerous and stressed cells. [1][2][3][4] In humans, cd T cells respond to chronic viral infections, as suggested by their robust proliferative capacity during EBV reactivation, 5 the upregulation of effector functions during HIV persistence, 6 increased CD69 expression and expansion of d1/d3 T cells in kidney transplant patients with associated CMV latency. 7 In addition, phosphoantigen-expanded human cd T cells upregulated IFN-c and cd T cells killed cells infected with human H1N1 and H5N1 influenza viruses.…”
Section: Introductionmentioning
confidence: 99%